THE ENVIRONMENTAL LAW ENFORCEMENT: IN THE FRAMEWORK OF POSITIVE LAW AND ISLAMIC LAW - Andi Abu Dzar Nuzul; Hamzah Hamzah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
The environmental law enforcement is a form of re-actualization of the hopes and dreams of a good living environment. The portion and content of positive law in environmental law enforcement are sufficient in ensnaring perpetrators of environmental destruction. In Islamic law, environmental enforcement is something that must be guarded and preserved, this is stated in the Qur'an and hadith. This study is a literature study, which examines the legislation on environmental enforcement and text arguments relating to the environment. The approach in this study is a formal juridical approach to the scale of positive law and a normative approach to Islamic law. The findings in this study prove that the rules regarding environmental law enforcement in positive law are very adequate. In Law Number 32 of 2009, it has accommodated acts of environmental destruction that can be ensnared with administrative, civil and criminal offenses that lead to fines and imprisonment. Meanwhile, in Islamic law, law enforcement against environmental destruction in jinayah law is subject to ta'zir punishment or a sentence stipulated by the government. In the concept of benefit, environmental destruction needs to be enforced because it is against the benefit of human life and/or can threaten the survival of mankind. The implication of this finding is that environmental law enforcement has been regulated in environmental legislation and is very adequate, and this is in line with the concept of negligence in Islamic law, so that environmental violations need to be taken firmly in order to maintain environmental sustainability. Keywords: Law enforcement; Environment; Positive Law; Islamic law.